Answer:
No
Step-by-step explanation:
Let's solve your equation step-by-step.
−2x−6=2x+6
Step 1: Subtract 2x from both sides.
−2x−6−2x=2x+6−2x
−4x−6=6
Step 2: Add 6 to both sides.
−4x−6+6=6+6
−4x=12
Step 3: Divide both sides by -4.
−4x/−4 = 12/-4
=
x=−3
2( coin faces) 8( number of times)
700/10 equals 70, so the answer is 70.
-6x + 3 + x - 7...when ur adding expressions such as this, and there is a plus sign in between them, the parenthesis are not needed.
we now combine like terms...
-6x + x = -5x
3 - 7 = -4
and we are left with : -5x - 4 <==